Prevalência do transtorno depressivo maior em pessoas com dependência química - Pereira, Pablo Michel Barcelos (2020)
Introduction: The identification of major depressive disorder (MDD) in people with chemical addiction is important for both the prognosis and for the planning and development of appropriate interventions. Since its concomitance can modify the signs and symptoms of each comorbidity, increasing the number of inappropriate therapeutic interventions and ineffectiveness. Objective: To verify the prevalence of major depressive disorder in people with chemical addiction admitted to therapeutic communities located in the south of Santa Catarina. Methods: The methodology used was a cross-sectional study. The research sites were therapeutic communities for individuals with chemical addiction, 184 individuals in total. The tests applied were the social questionnaire and the Structured Interview for disorders of DSM-V (items: E1-E36; A45-A61; A1-A12). Results: All patients did not attend a psychiatric consultation upon entering the institution and the majority did not undergo regular psychiatric consultation (94.5%). The assessment of disorders due substance abuse showed that 68.3% of participants had pure alcohol dependence as a reason for admission and 31.7% dependence on alcohol and other drugs. It was found that 89 participants (55.3%) had diagnostic criteria for major depressive disorder, and 59.1% of these had alcohol addiction (p <0.028). Also 60.2% of alcoholics fulfilled diagnostic criteria for severe alcohol dependence (p <0.028). Discussion: Studies have shown that the average MDD in drug addicts varies between 18 and 26%, the results of this research indicated twice more (55.3%), that is, the participants in this study have a higher prevalence of MDD compared to other national and international works. Conclusion: Given the above, it is seen that depression in the studied population must consolidate itself as an important variable for the effectiveness of the treatment, since its prevalence is high and has repercussions on the quality of life of the individuals and length of stay in the clinic.